What cultural aspects should be taught in FL lessons? – A model for evaluating the cultural content in FL course-books - Zuzana Sándorová (Acta Scientiarum. Language and Culture, 2021)
There is general agreement among intercultural scholars that FL course-books as dominant teaching materials have considerable influence on FL learners’ attitudes towards the target culture, as well as on their overall intercultural communicative competences (ICC). Therefore, in order to equip FL learners with the necessary intercultural knowledge and skills, much greater attention should be paid to the content of this fundamental didactic tool. A number of checklists and models have been elaborated in order to help to decide whether the particular teaching material has the potential to develop FL learners’ ICC. The present paper aims at summarising the results of document analyses that served to fine-tune the research instrument applied in a course-book package analysis. However, the findings of the research also provide a list of aspects that be treated in FL classrooms in order to develop learners’ ICC